Contributing factors to surgical site infection after tibial plateau leveling osteotomy: A follow‐up retrospective study. Issue 5 (2nd May 2020) - Hagen, Chris R. M.; Singh, Ameet; Weese, J. Scott; Marshall, Quinn; Linden, Alex zur; Gibson, Thomas W. G.
Abstract: Objective: To identify factors associated with surgical site infection (SSI) after tibial plateau leveling osteotomy (TPLO). Study design: Retrospective case series. Animals: Dogs (n = 541) that underwent TPLO (n = 659). Methods: Medical records of dogs that underwent TPLO from 2011‐2018 were reviewed. Data collected included perioperative and postoperative antimicrobial administration, stifle inspection, duration of surgery and anesthesia, comorbidities, and development of SSI including timing, microbiological investigation, and implant removal. Referring veterinarians were contacted for all dogs without a recorded return visit. Risk factors for SSI were assessed by using a multivariable logistic regression model built by using a stepwise approach. Results: Surgical site infection was documented in 71 of 659 (11%) TPLO, with methicillin‐resistant Staphylococcus pseudintermedius accounting for 20 of 71 (28%) infections. Protective factors against SSI included administration of postoperative antimicrobials (odds ratio [OR] 0.263; 95% CI = 0.157, 0.442) and timing of preoperative antimicrobial administration. Preoperative antimicrobial timing was protective against SSI when it was administered more than 60 minutes before the first incision compared with administration within 30 minutes (OR 0.275; 95% CI = 0.112, 0.676) or within 60 minutes (OR 0.419; 95% CI = 0.189, 0.929) of the first incision. Conclusion: Early administration of perioperative antimicrobials and postoperative antimicrobial administration were protective against SSI after TPLO. Clinical significance: Antimicrobials can influence the risk of SSI after TPLO. Perioperative and postoperative antimicrobial administration timing should be considered to reduce SSI.